La gamificación como estrategia didáctica para el fortalecimiento de la lectura comprensiva a nivel literal, en los estudiantes de quinto año de egb de la unidad educativa “María Auxiliadora” de la ciudad de Caluma, provincia Bolívar, periodo 2021 a 2022 - Morejón Ocampo, Diana Marisol (2022)
This research project was developed in the Maria Auxiliadora Educational Unit "Caluma" belonging to the province of Bolívar, where it has been developed to solve the difficulties regarding the lexical and semantic processes and the direct relationship with reading and writing that have each of the Fifth Year students of Basic General Education, who for many reasons have not managed to improve cognitive and linguistic skills, thus becoming a complex problem over time that prevents the acquisition of content and normal learning with the other years of schooling, for this reason the need arises to promote reading comprehension at a literal level, through the use of a new teaching-learning methodology such as gamification, since it will allow transferring teaching-learning through games in the educational field, with the sole purpose of increasing better results, where students are Students will be able to play online, accumulating points, climbing levels, obtaining prizes, gifts, rankings, challenges, missions or challenges. With this teaching technique, each student becomes the protagonist of their own learning, because children like to play and, in this way, students feel more comfortable playing and at the same time learning in a very dynamic and interactive way. The research methodology applied in this project was of a qualitative approach, since it has allowed to recompile processes and activities that help in learning, in the same way descriptive, exploratory and documentary research was used, since through them it allowed to carry out the study about the topic or research problem, however, inductive and deductive methods were also applied to support the issues of gamification in the educational field; In addition, the techniques and instruments of research such as observation, survey and interview were applied, allowing all possible information to be obtained within the Educational Unit mentioned above. Finally, the proposal includes the application of the gamification technique to improve the learning levels of the students, allowing them to strengthen their knowledge in reading comprehension at a literal level. Keywords: Gamification, Readin